(untitled) (ENTHYMEMA, 2022)
The article analyzes the role played by the journal "Na postu" in the marginalization of village literature. In the 1920s, the role played by this journal was more important than generally expected, because the editors were able to accelerate and in a certain way guide the government’s choices in the cultural sphere. As a result, an entire strand of Russian cultural tradition was obliterated. The village literature writers were slandered and then physically o socially liquidated or replaced with authors ideologically conforming to the new collective farm literature.